Epidemiological and clinical characteristics of congenital pseudarthrosis of the tibia in China - Zhou, Yijun; Tan, Qian; Liu, Kun; Liu, Yaoxi; Zhu, Guanghui; Mei, Haibo; Yang, Ge (Frontiers in Pediatrics, 2022)
Background: Congenital pseudarthrosis of the tibia (CPT) is a refractory and rare disease. Because of its extremely low incidence, little is known about its clinical features. In this retrospective study, we aim to analyze the clinical characteristics of patients with CPT. Methods: This is a retrospective study of children with CPT identified by radiological review. Investigations of CPT included general conditions, the characteristics of CPT, treatment methods and surgical complications. Results: We collected 514 CPT cases from 1999 to March 2020 in our hospital, including 317 (61.67%) boys, 197 (38.33%) girls; 330 (62.86%) in Crawford IV; 510 (97.14%) in mid and distal 1/3 tibia; 481 (93.58%) in less than 3 years at onset age; 297 (57.78%) in less than 3 years at first outpatient visit). The most common postoperative complication was ankle valgus (101, 39.60%), followed by limb length discrepancy（91, 35.69%), refracture (38, 14.90%), osteomyelitis (15, 5.88%) and removal of internal fixation (10,3.93%) . Conclusions: CPT with higher incidence of Crawford IV frequently occurs in boys and the middle or distal part of the tibia; most patients have the onset age and first outpatient visit before 3 years; the major surgical complications are ankle valgus and limb length discrepancy.